Assertive outreach - Firn, M; Burns, T (2004)
Assertive outreach has become established as a valuable form of care delivery for the severely mentally ill. Not only does it keep a focus on the most difficult to engage patients, but it has introduced greater clarity to the organization and evaluation of metal health teams. The model is described, together with its historical and international context, and a realistic assessment of model fidelity issues. Assertive outreach is a labour-intensive, 7-day-a-week service commitment, which aims to support basic survival needs, but is also highly compatible with more sophisticated evidence-based interventions for psychosis. Interventions need to be delivered in a way that is acceptable in the long term to patients and their families. In assertive outreach this means much more than simply taking the service to the individual. It means engaging in a constructive long-term relationships, and flexibility in roles and relationships beyond the mere professional. Teams use small caseloads, a team approach and generic working to meet the majority of needs, including practical help and social care, medication and psychological interventions. These interventions, with a review of the supporting research outcomes for assertive outreach implementation, are described. © 2004 Elsevier Ltd. All rights reserved.